Pengaruh Perputaran Modal Kerja, Perputaran Persediaan, Perputaran Piutang, Perputaran Kas terhadap Likuiditas Perusahaan. (Literature Review Manajamen Keuangan ) - Belantika Sheren Aurorita; Muhammad Reza Adi Nugroho; Ramdhani Ahmad Fariz Putra Setiawan; Wiwin Aini Syifa; Tri Yulaeli (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Economic growth is increasing rapidly so that the problems faced by companies and business fields are increasingly complex and dynamic. One of the problems faced by companies and the business sector is financial problems. Good working capital management is very necessary to achieve company goals and business fields as reflected in the Effect of Working Capital Turnover, Inventory Turnover, Accounts Receivable Turnover, Cash Turnover on Company Liquidity obtained by the company. This study aims to determine whether turnover in working capital, accounts receivable, and inventories will affect a company's liquidity. Writing this literature review aims to build hypotheses of the influence between variables to be used in further research. This article discusses the influence of Working Capital Turnover, Inventory Turnover, Accounts Receivable Turnover, Cash Turnover on Company Liquidity, an introductory financial management literature study. Writing this literature review aims to build hypotheses of the influence between variables to be used in further research.